AKIBAT HUKUM BAGI NOTARIS DAN AKTA YANG DIBUATNYA TERKAIT ADANYA KETERANGAN PALSU DALAM AKTA BERITA ACARA RAPAT UMUM PEMEGANG SAHAM YANG BERKAITAN DENGAN PENGALIHAN SAHAM PERSEROAN - SARAH SARAH (PREMISE LAW JURNAL, 2019)
Dosen pembimbing:1. Prof. Dr. Madiasa Ablizar, SH, MS2. Notaris Dr. Suprayitno SH, MKn3. Dr. Muhd. Hamdan, SH, MHum A notary has to be truthful, honest, careful, independent, and impartial as stated in Article 16 paragraph (1) letter and a Article 4 of Law on Role of Notary. A noatry who is untruthful is sanctioned. Notary's untruthfulness in carrying out his duties as a public official can result in fraudulent statements in authentic deeds, notary in making Articles of Association of a company and changes to it, how about the position of the Deed of Minutes of Shareholder Meeting containing legal defects observed from the perspective of the Law No. 40/2007. This is a normative juridical research which is analytically descriptive. It uses secondary data collected through library research. The data are analyzed by Qualitative analysis and the conclusion is drawn deductively. The results of the research demonstrative that the authority of a notary makiing Articles of Association and changes to it is used in form of a noatrial deed as stipulated in the provision of the Law notarial authentic deeds is not subject to the Law on Role of Notary and the procedures of making decisions in Shareholder Meeting is pursuant to the Law on Limited liability companies, so that the deeds made are null and void. The legal consequences for such deeds have impacts on notary's liability for his actions in which he is sentenced with criminal sanction. Keywords: Akibat Hukum, Notaris, Akta Berita Acara Rapat Umum Pemegang Saham